2016
DOI: 10.1088/2053-1591/3/3/036401
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of high pressure sputtering for amorphous silicon deposition

Abstract: Amorphous silicon thin films were deposited using the high pressure sputtering (HPS) technique to study the influence of deposition parameters on film composition, presence of impurities, atomic bonding characteristics and optical properties. An optical emission spectroscopy (OES) system has been used to identify the different species present in the plasma in order to obtain appropriate conditions to deposit high purity films. Composition measurements in agreement with the OES information showed impurities whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Most Ga 2 O 3 /GaN heterointerfaces were developed by depositing Ga 2 O 3 on the GaN surface utilizing numerous techniques such as metalorganic chemical vapour deposition (MOCVD), sputtering, thermal oxidation, and pulse laser deposition. , Among various approaches, MOCVD has the demerit of using hazardous precursors that restrict the feasibility of mass production . Also, while depositing the film using sputtering and pulsed laser deposition (PLD), the substrate surface preparation may be critical in determining the adhesion; the setup cost is also very high. , On the other hand, thermal oxidation is a simple and convenient method for creating oxides directly on the substrate. This technique can minimize physical damage induced by plasma processing and undesirable contaminants from foreign elements of the deposited film. ,, Wolter et al demonstrated thermal annealing of GaN at 900 °C, which leads to the synthesis of bulk Ga 2 O 3 on GaN.…”
Section: Introductionmentioning
confidence: 99%
“…Most Ga 2 O 3 /GaN heterointerfaces were developed by depositing Ga 2 O 3 on the GaN surface utilizing numerous techniques such as metalorganic chemical vapour deposition (MOCVD), sputtering, thermal oxidation, and pulse laser deposition. , Among various approaches, MOCVD has the demerit of using hazardous precursors that restrict the feasibility of mass production . Also, while depositing the film using sputtering and pulsed laser deposition (PLD), the substrate surface preparation may be critical in determining the adhesion; the setup cost is also very high. , On the other hand, thermal oxidation is a simple and convenient method for creating oxides directly on the substrate. This technique can minimize physical damage induced by plasma processing and undesirable contaminants from foreign elements of the deposited film. ,, Wolter et al demonstrated thermal annealing of GaN at 900 °C, which leads to the synthesis of bulk Ga 2 O 3 on GaN.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we used the electron cyclotron resonance chemical vapor deposition (ECR-CVD) technique to deposit the a-Si:H, which is a remote plasma procedure [6] that could reduce the damage to the c-Si surface. Other advantages of ECR-CVD are the possibility of in situ substrate plasma pretreatment [7] and low processing pressure, which permits minimizing the contamination of the growing film [8]. The possibility for scaling-up makes the ECR-CVD a very attractive technique for commercial solar cell fabrication.…”
Section: Introductionmentioning
confidence: 99%